Examining geodetic glacier mass balance in the eastern Pamir transition zone. Issue 260 (3rd December 2020) - Lv, Mingyang; Quincey, Duncan J.; Guo, Huadong; King, Owen; Liu, Guang; Yan, Shiyong; Lu, Xiancai; Ruan, Zhixing
Abstract: Glaciers in the eastern Pamir have reportedly been gaining mass during recent decades, even though glaciers in most other regions in High Mountain Asia have been in recession. Questions still remain about whether the trend is strengthening or weakening, and how far the positive balances extend into the eastern Pamir. To address these gaps, we use three different digital elevation models to reconstruct glacier surface elevation changes over two periods (2000–09 and 2000–15/16). We characterize the eastern Pamir as a zone of transition from positive to negative mass balance with the boundary lying at the northern end of Kongur Tagh, and find that glaciers situated at higher elevations are those with the most positive balances. Most (67% of 55) glaciers displayed a net mass gain since the 21st century. This led to an increasing regional geodetic glacier mass balance from −0.06 ± 0.16 m w.e. a −1 in 2000–09 to 0.06 ± 0.04 m w.e. a −1 in 2000–15/16. Surge-type glaciers, which are prevalent in the eastern Pamir, showed fluctuations in mass balance on an individual scale during and after surges, but no statistical difference compared to non-surge-type glaciers when aggregated across the region.